Ejaculatory physiology and pathophysiology: assessment and treatment in male infertility - Revenig, Louis; Leung, Andrew; Hsiao, Wayland (Translational Andrology and Urology, 2014)
Azoospermia is a heterogeneous condition with multiple etiologies and a variety of treatments. In this chapter we present a summary of retrograde ejaculation and anejaculation, both of which are characterized by an absence of antegrade semen propulsion through the male reproductive tract. Each of these affects fertility, but is pathophysiologically distinct disorders with differing evaluation and treatment. Retrograde ejaculation has a myriad of well-characterized causes, from pharmacologic disruption to interference of neural mechanisms by surgical intervention for a variety of diseases. Medication is the mainstay of treatment, although only a minority responds and develops antegrade ejaculation. For the men who are not responders to medical therapy, but still have fertility goals, there are a variety of sperm retrieval techniques to assist their reproductive abilities. Failure of emission is characterized by an absence of the emission phase and no antegrade or retrograde expulsion of ejaculatory products. If fertility is desired, these men must rely on assisted ejaculatory procedures, and treatment choice is guided by etiology and response. Ultimately, retrograde ejaculation and failure of emission are in a spectrum of ejaculatory disorders which impair male fertility.